Malettinin E, an antibacterial and antifungal tropolone produced by a marine Cladosporium strain - Silber, Johanna; Ohlendorf, Birgit; Labes, Antje; Wenzel-Storjohann, Arlette; Näther, Christian; Imhoff, Johannes F. (Frontiers in Marine Science, 2014)
The isolation and structure elucidation of malettinins A–C (1–3) along with the new malettinin E (4) are described. The compounds were produced by the fungus Cladosporium sp. strain KF501, which was isolated from the German Wadden Sea. The malettinins are built up of tropolone/dihydropyran ring structures linked to a furan ring. The structure elucidation of the isolated compounds was achieved by means of one- and two-dimensional NMR spectroscopy supported by mass and UV data. The relative configuration of 4 was determined on the basis of single-crystal X-ray diffraction analysis. 1–4 exhibited antibacterial and antifungal activities when profiled against Xanthomonas campestris and Trichophyton rubrum. The influence of the chemical structure of the furan ring and of configurational changes on biological activities was observed.